NILAI–NILAI PENDIDIKAN ISLAM YANG TERDAPAT DALAM HADIS ANJURAN AZAN DAN QOMAT KETIKA KELAHIRAN ANAK - Robi'ah (Institut Darul Falah Bandung Barat, 2025)
This article aims to identify the values ​​of religious moderation in Gurindam Dua Belas by Raja Ali Haji and examine its contribution to the field of Islamic education. The study employs a qualitative approach, utilizing content analysis of the verses in the Gurindam, which is interpreted based on the principles of religious moderation outlined by the Indonesian Ministry of Religious Affairs. The findings reveal that Gurindam Dua Belas conveys strong moral messages that remain highly relevant in contemporary life, particularly the values ​​of tawassuth (balance), tasâmuh (tolerance), i'tidal (justice), and shura (deliberation). These values ​​align with the objectives of character education and the development of Aqidah Akhlak learning in schools. Furthermore, the work makes practical contributions by offering opportunities to integrate Islamic values into Indonesian language learning, incorporating Islamic nuances, and exploring Islamic Religious Education subjects. Thus, Gurindam Dua Belas functions not only as a Malay literary heritage but also as an educational medium to instill moderate, inclusive, and virtuous attitudes among students. This article emphasizes the significance of revitalizing local literary works as contextual learning resources to foster Islamic character, aligning with the vision of Islamic education in Indonesia.